Clinical efficacy of resin infiltration technique alone or in combination with micro abrasion and in-office bleaching in adults with mild-to-moderate fluorosis stains - Poorvi Saxena; Mandeep S Grewal; Pamita Agarwal; Gagandeep Kaur; Jayant Verma; Vandana Chhikara (Wolters Kluwer Medknow Publications, 2021)
Background: The present study was conducted to evaluate the clinical efficacy of resin infiltration technique alone or in combination with microabrasion and in-office bleaching in adults with mild-to-moderate fluorosis stains on permanent maxillary anterior teeth at the end of 1 month. Materials and Methods: A total of 30 patients with nonpitted fluorosis stains on maxillary anterior were classified as mild (n = 15) and moderate (n = 15). Each grade is subdivided into three groups as Group A, Group B, and Group C. Group 1: Mild (score 2), Subgroup A: Resin infiltration (n = 5 patients), Subgroup B: Microabrasion followed by resin infiltration (n = 5 patients), Subgroup C: Microabrasion and bleaching followed by resin infiltration after 2 weeks (n = 5 patients). Group 2: Moderate (score 3), Subgroup A: Resin infiltration (n = 5 patients), Subgroup B: Microabrasion followed by resin infiltration (n = 5 patients), and Subgroup C: Microabrasion and bleaching followed by resin infiltration after 2 weeks (n = 5 patients). Microabrasion was performed with the opalustre kit from Ultradent according to the manufacturer's instructions. Pola office bleaching from SDI and Icon infiltrant was performed. Stain score, improvement in appearance score, need for further treatment, patient satisfaction score, tooth sensitivity immediately after treatment, 24 h and 72 h were recorded. Results: The mean appearance score in Group 1A was 73.60, in Group 1B was 72.87, in Group 1C was 65.27, in Group 2A was 68.00, in Group 2Bwas 72.93 and in Group 2C was 84.73. The mean need for further treatment score in Group 1A was 72.80, in Group 1B was 78.40, in Group 1C was 68.73, in Group 2A was 71.20, in Group 2B was 79.53 and in Group 2C was 88.73. The mean patient satisfaction score in Group 1A was 91.40, in Group 1B was 95.20, in Group 1C was 98.00, in Group 2A was 90.20, in Group 2B was 99.40 and in Group 2C was 100.00. There was a significant difference in mean tooth sensitivity immediately after treatment between Groups 1A, 1B, 1C, 2A, 2B, and 2C. There was a significant difference in mean tooth sensitivity after 24 h between Groups 1A, 1B, 1C, 2A, 2B, and 2C. Conclusion: Resin infiltration technique in combination with bleaching and microabrasion technique found to be effective in the management of dental fluorosis.